Effect of aerobic exercise on cognition in younger adults: A randomized clinical trial. (26th February 2019) - Stern, Yaakov; MacKay-Brandt, Anna; Lee, Seonjoo; McKinley, Paula; McIntyre, Kathleen; Razlighi, Qolamreza; Agarunov, Emil; Bartels, Matthew; Sloan, Richard P.
Abstract : Objective: To determine efficacy of aerobic exercise for cognitive function in younger healthy adults. Methods: In a randomized, parallel-group, observer-masked, community-based clinical trial, 132 cognitively normal individuals aged 20–67 with below median aerobic capacity were randomly assigned to one of two 6-month, 4-times-weekly conditions: aerobic exercise and stretching/toning. Efficacy measures included aerobic capacity; cognitive function in several domains (executive function, episodic memory, processing speed, language, and attention), everyday function, body mass index (BMI), and cortical thickness. Results: Aerobic capacity increased significantly (β = 2.718; p = 0.003), and BMI decreased significantly (β = −0.596; p = 0.013) in the aerobic exercise but not in the stretching/toning condition. Executive function improved significantly in the aerobic exercise condition; this effect was moderated by age (β = 0.018 SD/y; p = 0.028). At age 40, the executive function measure increased by 0.228 SD (95% confidence interval [CI] 0.007–0.448), and by 0.596 SD (95% CI 0.219–0.973) at age 60. Cortical thickness increased significantly in the aerobic exercise group in a left frontal region and did not interact with age. Controlling for age and baseline performance, individuals with at least one APOE ε4 allele showed less improvement in executive function with aerobic exercise (β = 0.5129, 95% CI 0.0381–0.988; p = 0.0346). Conclusions: This randomized clinical trial demonstrates the efficacy of aerobic exercise for cognition in adults age 20–67. The effect of aerobic exercise on executive function was more pronounced as age increased, suggesting that it may mitigate age-related declines. Increased cortical thickness suggests that aerobic exercise contributes to brain health in individuals as young as age 20. Clinicaltrials.gov identifier: NCT01179958. Classification of evidence: This study provides Class II evidence that for adults age 20–67 with below median aerobic capacity, aerobic exercise significantly improves executive function but not other measures of cognitive function.